Omnibus Law Cipta Kerja Perspektif Hukum Islam - Harmono, Harmono; Abdulah Pakarti, Muhammad Husni; Judijanto, Loso; Kadir, Taqyuddin; Gunawan, Moh Sigit (Direktorat Jenderal Peraturan Perundang-undang, Kementerian Hukum, 2024)
This law has a significant impact on various aspects of people's lives, including the economy, labor, and the environment. This study aims to analyze the Omnibus Law on Job Creation from an Islamic perspective with a focus on aspects of social justice, protection of workers' rights, and environmental impacts. However, the problems are (1) How is the Islamic perspective on social justice regulated in the Omnibus Law on Job Creation Law? (2) How is the protection of workers' rights in the Omnibus Law on Job Creation Law seen from an Islamic perspective? (3) How is the environmental impact of the implementation of the Omnibus Law on Job Creation Law from an Islamic perspective?. This research uses a normative juridical method with a qualitative approach as well as conceptual and statutory regulations (normative-juridical). By analyzing legal documents, and Islamic literature, related to the Omnibus Law on Job Creation Law. This approach will help in understanding aspects of social justice, protection of workers' rights, and environmental impacts associated with the law. The results show that, although the Omnibus Law on Job Creation is designed for the public good with the aim of promoting economic growth and job creation, there are discrepancies with the principles of Islamic Law, particularly in terms of social justice, welfare, and protection of workers' rights. Some of the rules in this law tend to favor employers, which can be detrimental to workers and society, and contradict the concept of justice in Islam. In addition, the negative impact on the environment that may arise from the implementation of this law is also not in line with Islamic principles that emphasize the importance of preserving nature and the balance of the ecosystem.